Beyond the gut: spectrum of magnetic surgery devices - Lee, William G.; Evans, Lauren L.; Harrison, Michael R. (Frontiers in Surgery, 2023)
Since the 1970s, magnetic force has been used to augment modern surgical techniques with the aims of minimizing surgical trauma and optimizing minimally-invasive systems. The majority of current clinical applications for magnetic surgery are largely centered around gastrointestinal usessuch as gastrointestinal or bilioenteric anastomosis creation, stricturoplasty, sphincter augmentation, and the guidance of nasoenteric feeding tubes. However, as the field of magnetic surgery continues to advance, the development and clinical implementation of magnetic devices has expanded to treat a variety of non-gastrointestinal disorders including musculoskeletal (pectus excavatum, scoliosis), respiratory (obstructive sleep apnea), cardiovascular (coronary artery stenosis, end-stage renal disease), and genitourinary (stricture, nephrolithiasis) conditions. The purpose of this review is to discuss the current state of innovative magnetic surgical devices under clinical investigation or commercially available for the treatment of non-gastrointestinal disorders.